Incidence of microplastics in personal care products: An appreciable part of plastic pollution - Sun, Qing; Ren, Shu-Yan; Ni, Hong-Gang (The Science of the total environment, 2020)
Microplastic had been commonly used in personal care products (PCPs) until it was documented to be a pollutant. The relative contents of microplastics in PCPs decrease in the order of the USA, Europe, and Asia. The geometric means of the abundance and mass of microplastics found in PCPs were 2162 particles/g and 0.04 g/g, respectively. Diameters of PCP-derived microplastics are less than 350 μm. To quantify the exact contribution of PCPs to microplastic pollution, this review surveyed the existing scientific literature and statistically integrated the findings from 88 literatures. Overall, approximately 1500 tons/year of microplastics from PCPs escape from WWTPs and enter the global aquatic environment. According to the PCP consumption and microplastics levels, the mass emission of global PCP-derived microplastics reach up to 1.2 × 104 tons/year. The two figures account for ~0.1% and ~ 0.8% of the annual global release of primary microplastics in the world oceans (~1.5 × 106 tons/year). In the last 50 years (1970–2019), up to 3.00 × 105 tons of PCP-derived microplastics have accumulated in the environment. The main plastic in PCPs is polyethylene, which is known for being a remarkably resistant polymer to degradation. Even if microbeads are completely banned globally in 2020, microplastics that have been discharged into the environment will still persist for a long time and claim our highest attention. This review provided primary information to deal effectively with the problem of PCP-derived microplastic both now and in the future. [Display omitted] •The density of microplastics in PCPs showed lognormal or gamma distribution.•Microplastic in PCPs is an appreciable part of plastic pollution.•About 1500 tons/year of microplastics from PCPs enter the global aquatic environment.•Global PCP-derived microplastics reach up to 1.2 × 104 tons/year.•Emission of PCP-derived microplastics in the last 50 years reached up to 3.0 × 105 tons.